Political Partisanship Alters the Causality Implicit in Verb Meaning. (October 2019) - Niemi, Laura; Roussos, Gina; Young, Liane
This research adapted the implicit causality task from psycholinguistics to investigate the politics of attribution during the 2016 U.S. Presidential Election. Results showed that both Hillary Clinton and Donald Trump supporters judged their preferred candidate as causal for positive events and their nonpreferred candidate as causal for negative events, indicating an important role for political candidate support in causal attribution, alongside lexical semantics. The findings demonstrate the social psychological utility of the implicit causality task and contribute to our understanding of broadly shared and largely untracked extralinguistic influences on causal attribution.